Theoretical and experimental models of catalysts for selective synthesis of metallic single-walled carbon nanotubes and their electrochemical capacitance - Zuru, Danlami Umar (2017)
A major challenge in the field of carbon nanotubes (CNTs) synthesis via Chemical Vapour Deposition (CVD) method is lack of established theoretical model for the selection and design of metal/support catalysts to grow single wall carbon nanotubes (SWCNTs) of desired electronic types. This has limited the application of these materials in electronics, specifically as electrodes for supercapacitor. In the current report, Theoretical Model 1 (DH1) was proposed and developed via kinetic theory, by correlating decompositions of carbon precursors with active metal electrons and applied in the selection of carbon feedstock and metal catalyst matrix. Theoretical Model 2 (DH2) was a proposed modification of the Extended Tight Binding (ETB) model equations, developed by introducing circumferential and axial distortions to diameter and chiral angles of SWCNTs, respectively, which was then applied in predicting the selection and design of metal/support catalyst matrix. Outcomes of these models conformed with advances in heterogeneous catalysis and CNT synthesis, and were employed in the design and preparation of four Fe2O3/Al2O3 catalyst samples each, with compositions A (11, 8), B (10, 4), C (10, 7) and D (8, 8) where (n, m) are the chiral index of each SWCNT. This was achieved via impregnation of Fe(NO3)3.9H2O and Al(NO3)3.9H2O precursor salts, calcined at 450oC. Optimized parameters of the CVD processes for the synthesis of the corresponding CNTs were achieved at 1000oC working temperature, 0.5 g catalyst loading and 30 min pyrolysis of C6H14/N2 feedstock. Field Emission Scanning Electron Microscopy (FESEM) images of the catalyst samples showed spherical nano sized particles and resulting Energy Dispersive Spectroscopy (EDS) indicated the presence of only Fe, Al, and O elements. X-ray Diffraction (XRD) analysis revealed α-Fe2O3 phases in which Al2O3were incorporated, with average crystallite size of 27 nm. BET surface area analysis of catalysts A, B, C and D revealed surface area (m2 g-1) of 170, 205, 172 and 153, respectively, with average pore diameter of 4 nm, suggesting mesoporosity. Transmission Electron Microscopy (TEM) and FESEM images of the as-grown CNTs shows densely entangled bundles, while High Resolution Transmission Electron Microscopy analysis (HR-TEM) confirmed arrangement of SWCNTs in the bundles. XRD analysis indicated peaks of highly graphitized carbon atoms, Fe3C, FeN and Al4C3, suggesting that CNT growth might have occurred on reduced metal atoms, as predicted in DH2. Raman analysis of the CNT samples revealed that the Radial Breathing Modes (RBMs), diameter and energy band gaps of the samples were in conformity with those of ETB model. Fourier Transformed Infra-Red (FT-IR) analysis of the four samples confirmed the stretching and bending vibrations of amide carbonyl (-C=ONHR) and carboxylic (-COOH) functional groups, respectively, in all the samples, indicating that the samples were successfully functionalized. Highest electrochemical abilities of the SWCNT samples were observed in 0.1 M KCl electrolyte, tested from -1.0 to 1.0 V potential window and from scan rate of 0.01 to 0.2 V s-1. Specific capacitance (F g-1) of 242, 207, 284 and 259 were recorded for SWCNTs A4, B4, C4 and D4, respectively. All samples showed stable pseudocapacitive cyclic voltammograms, straight charge-discharge profiles, sustained 1000 cycle test and enhanced current-potential responses which suggested good potential for pseudocapacitor electrodes.